Severity of overactive bladder symptoms and response to dose escalation in a randomized, double‐blind trial of solifenacin (SUNRISE). (7th January 2013) - Cardozo, Linda; Amarenco, Gerard; Pushkar, Dmitry; Mikulas, Jura; Drogendijk, Ted; Wright, Mark; Compion, Gerhard
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Antimuscarinics are effective and well tolerated for treatment of OAB. Studies have found that a flexible dosing strategy can be effective in improving OAB symptoms with minimal impact on tolerability. This study confirms these findings with two doses of solifenacin, and shows that improved outcomes can be achieved by increasing solifenacin dose (from 5 to 10 mg) in patients with more severe symptoms. Objective To determine the relationship between severity of baseline overactive bladder (OAB) symptoms and requests for solifenacin dose increases, and the efficacy of 5 and 10 mg solifenacin doses in relieving OAB symptoms in patients who requested a dose increase. Patients and Methods In a 16‐week clinical study, patients with OAB were randomized to double‐blind treatment with solifenacin or placebo once daily. At week 8, all patients could request a dose increase; these patients entered a second phase of 8 weeks in which those in the solifenacin group were randomized to either 5 or 10 mg doses. The primary efficacy variable was mean change in the number of urgency episodes with or without incontinence per 24 h, measured using the Patient Perception of Intensity of Urgency Scale (PPIUS; grades 3 and 4). Results Of 591 patients receiving solifenacin at 8 weeks, 275 (46.5%) requested a dose increase to 10 mg, and were further randomized to receive 10 mg (n = 140) or to remain on 5 mg (n = 135). Patients who requested a dose increase at week 8 generally had more severe OAB symptoms at baseline and a smaller response at week 8 to the initial solifenacin 5 mg dosage than those who did not. Greater reductions in the mean number of severe urgency episodes (PPIUS grades 3 and 4) were observed from week 8 to the end of treatment for patients requesting a dose increase and randomized to 10 mg solifenacin compared with those randomized to remain on 5 mg (mean reductions –0.9 vs –0.4, respectively), although these did not reach statistical significance. Statistically significant reductions were observed in mean total urgency score (TUS; –2.7 vs –0.6; P = 0.010), mean maximum PPIUS urgency rating (–0.3 vs –0.1; P = 0.034) and mean micturition frequency (–0.8 vs –0.1; P = 0.037). For all other OAB variables, greater changes were observed in the solifenacin 10 mg group but these did not reach statistical significance. Of those who requested a dose increase, eight (5.7%) patients randomized to receive 10 mg and one (0.7%) patient randomized to remain on 5 mg reported new or worsening cases of dry mouth. Conclusions Increasing the solifenacin dose to 10 mg further improved OAB symptoms in patients who requested a dose increase after 8 weeks' treatment with 5 mg solifenacin. The present study supports the view that patients with severe OAB symptoms benefit from a higher antimuscarinic dose.